Effects of oxidation on copper-binding properties of Aβ1-16 peptide: A pulse radiolysis study. (December 2013) - Ramteke, S. N.; Ginotra, Y. P.; Walke, G. R.; Joshi, B. N.; Kumbhar, A. S.; Rapole, S.; Kulkarni, P. P.
Abstract: The reaction of hydroxyl radicals ( OH) with Aβ1-16 peptide was carried out using pulse radiolysis to understand the effect of oxidation of peptide on its copper-binding properties. This reaction produced oxidized, dimeric and trimeric Aβ1-16 peptide species. The formation of these products was established with the help of fluorescence spectroscopy and mass spectrometry. The mass spectral data indicate that the major site of oxidation is at His6, while the site for dimerization is at Tyr10. Diethyl pyrocarbonate-treated Aβ1-16 peptide did not produce any trimeric species upon oxidation with OH. The quantitative chemical modification studies indicated that one of the three histidine residues is covalently modified during pulse radiolysis. The copper-binding studies of the oxidized peptide revealed that it has similar copper-binding properties as the unoxidized peptide. Further, the cytotoxicity studies point out that both oxidized and unoxidized Aβ1-16 peptide are equally efficient in producing free radicals in presence of copper and ascorbate that resulted in comparable cell death.